REWAS 2019 Manufacturing the Circular Materials Economy - Gaustad, Gabrielle; Fleuriault, Camille; Gökelma, Mertol; Howarter, John A.; Kirchain, Randolph; Ma, Kaka.; Meskers, Christina; Neelameggham, Neale R.; Olivetti, Elsa.; Powell, Adam C.; Tesfaye, Fiseha; Verhulst, Dirk.; et al. (Cham : Springer International Publishing : Imprint: Springer, 2019)
Every sector faces unique challenges in the transition to sustainability. Across each, materials will play a key role. That will depend on novel materials and processes, but these will only be effective with a solid understanding of the trends in the market. For each respective sector, the papers in this collection will explore the trends and drivers toward sustainability, the enabling materials technologies and challenges, and the tools to evaluate their implications. Major sections in REWAS 2019 include: Disruptive Material Manufacturing: Scaling and Systems Challenges Education and Workforce Development Rethinking Production Secondary and Byproduct Sources of Materials, Minerals, and Metals.
Disruptive Material Manufacturing: Scaling and Systems Challenges -- Education and Workforce Development -- Rethinking Production -- Secondary and Byproduct Sources of Materials, Minerals, and Metals.
Keywords: Materials -- Analysis; Refuse and refuse disposal; Materials; Characterization and Analytical Technique; Waste Management/Waste Technology; Materials Engineering